Psychological analysis of the image of charismatic personality in modern youth in the context of the problem of self-design (Actual Problems of Psychology in Educational Institutions, 2019)
The paper dwells on the analysis of the problem of image ofcharismatic personality in modern youth in the context of the project paradigm.The author examines the psychological content and main components of thisconcept, from the point of view of various scientific schools. The paperelucidates the results of empirical research of the representation of young menabout the image of a charismatic personality, namely: understanding the contentof this concept, its main characteristics and components, values, motivations ofbehavior. In addition, the researchers expressed their opinion on the possibilityof developing charisma as an important component of self-design in eachpersonality
Keywords: charisma, charismatic personality, structure of charisma, qualities of a charismatic personality, designing qualities of a charismatic personality